PELATIHAN OPERASIONAL PERBANKAN SYARIAH BAGI KSPPS BMT PENITI KAHURIPAN MULIYA - Khalifaturofi'ah, Sholikha Oktavi; Adiba, Elfira Maya; Nasution, Zubaidah (Jurnal Terapan Abdimas, 2021)
Abstract. One of the problems in Islamic microfinance institutions is the availability of human resources who understand and are qualified in Islamic banking operations. The development of professionalism of lecturers in the field of teaching regarding Islamic bank operation laboratories has been related to the problem of lackof understanding of human resources in BMT. The purpose of this activity is to provide training on Islamic banking operations. This training was attended by 5 employees of KSPPS BMT Peniti Kahuripan Muliya. The training participants came from three BMT branch offices, namely the Surabaya branch, the Boyolalibranch, and the Bandung branch. The methods used are 1) providing theoretical and practical knowledge about Islamic banking operations 2) assistance in the roleplay of Islamic banking operations. The results of this activity are: First, all participants of this training activity are very enthusiastic and highly motivated to participate in the implementation of Islamic banking operational training activities. Second, the participants who attended the training as a whole were 60% of all training participants.Abstrak. Salah satu masalah dalam lembaga keuangan mikro syariah adalah ketersediaan SDM yang memahami dan mumpuni dalam operasional perbankan syariah. Pengembangan profesionalisme dosen pada bidang pengajaran tentang laboratorium operasi bank syariah selama ini terkait dengan persoalan kurangnya pemahaman SDM di BMT. Tujuan kegiatan ini adalah untuk memberikan pelatihan tentang operasional perbankan syariah. Pelatihan ini diikuti oleh para karyawan KSPPS BMT Peniti kahuripan Muliya sebanyak 5 orang. Peserta pelatihan berasal dari tiga kantor cabang BMT yaitu cabang Surabaya, cabang Boyolali, dan Cabang Bandung. Metode yang digunakan adalah 1) pemberian pengetahuan teoretis dan praktis tentang operasional perbankan syariah 2) pendampingan dalam roleplay operasional perbankan syariah. Hasil kegiatan ini adalah : Pertama, semua peserta kegiatan pelatihan ini sangat antusias, bersemangat, dan mempunyai motivasi yang tinggi mengikuti pelaksanaan kegiatan pelatihan operasional perbankan syariah. Kedua, peserta kegiatan yang mengikuti pelatihan secara keseluruhan adalah 60% dari semua peserta pelatihan.